Hubungan Lower Urinary Tract Symptoms (LUTS) dengan Kualitas Hidup Pasien Benigna Prostatic Hyperplasia (BPH) - Ipnamelti Ipnamelti; Bayhakki Bayhakki; Yesi Hasneli N (Malahayati Nursing Journal, 2025)
ABSTRACT Benign Prostatic Hyperplasia (BPH) is a non-life-threatening condition that significantly impacts the quality of life of affected individuals. Patients with BPH commonly experience symptoms such as nocturia, increased frequency and urgency of urination, decreased urine flow rate, incomplete bladder emptying, and hesitancy to urinate (Lower Urinary Tract Symptoms/LUTS). LUTS directly impairs the quality of life of BPH patients and contributes to morbidity. The severity of LUTS in BPH patients can be subjectively assessed using the International Prostate Symptom Score (IPSS). This study aims to explore the relationship between Lower Urinary Tract Symptoms (LUTS) and quality of life in patients with Benign Prostatic Hyperplasia (BPH). This study employed a quantitative approach with a descriptive correlational design using a Cross-Sectional approach. The population consisted of all patients diagnosed with Benign Prostatic Hyperplasia (BPH) experiencing Lower Urinary Tract Symptoms (LUTS) at RSUD Arifin Achmad Provincial Hospital in Riau from October to December 2023, totaling 153 individuals. A purposive sampling technique was used to select 111 participants as the study sample. Bivariate analysis using the chi-square test was employed for data analysis. Among the respondents, 43 individuals (38.74%) were categorized with moderate LUTS. The quality of life of BPH patients was rated as moderate in 62 respondents (55.86%). The Pearson Chi-Square test yielded a p-value of 0.003 (p-value α (0.05)). There is a significant relationship between Lower Urinary Tract Symptoms (LUTS) and the quality of life of patients with Benign Prostatic Hyperplasia (BPH) at RSUD Arifin Achmad Provincial Hospital in Riau. Keywords: Lower Urinary Tract Symptoms, Quality of Life, Benigna Prostatic Hyperplasia  ABSTRAK Benign Prostatic Hyperplasia (BPH) merupakan kondisi yang tidak mengancam jiwa namun memberikan dampak signifikan terhadap kualitas hidup penderitanya. Penderita BPH umumnya mengalami gejala seperti nokturia, peningkatan frekuensi dan urgensi buang air kecil, penurunan laju aliran urin, kesulitan mengosongkan kandung kemih secara sempurna, dan keraguan saat ingin buang air kecil (Lower Urinary Tract Symptoms/LUTS). LUTS secara langsung mempengaruhi kualitas hidup penderita BPH dan berkontribusi terhadap morbiditas. Derajat keparahan LUTS pada penderita BPH dapat dinilai secara subjektif menggunakan International Prostate Symptom Score (IPSS). Penelitian ini bertujuan untuk mengeksplorasi hubungan antara Lower Urinary Tract Symptoms (LUTS) dan kualitas hidup pada pasien Benign Prostatic Hyperplasia (BPH). Penelitian ini menggunakan pendekatan kuantitatif dengan desain deskriptif korelasional melalui pendekatan Cross Sectional. Populasi penelitian terdiri dari seluruh pasien Benign Prostatic Hyperplasia (BPH) yang mengalami Lower Urinary Tract Symptoms (LUTS) di Rumah Sakit Umum Daerah (RSUD) Arifin Achmad Provinsi Riau pada bulan Oktober hingga Desember 2023, dengan jumlah 153 orang. Sampel penelitian sebanyak 111 orang dipilih dengan menggunakan teknik purposive sampling. Analisis data dilakukan dengan menggunakan analisis bivariat menggunakan uji chi-square. Dari responden, sebanyak 43 orang (38,74%) mengalami LUTS dengan derajat sedang. Kualitas hidup pasien BPH dinilai sebagai sedang oleh 62 responden (55,86%). Uji Pearson Chi Square menunjukkan nilai p-value sebesar 0,003 (p-value α (0,05)). Terdapat hubungan yang signifikan antara Lower Urinary Tract Symptoms (LUTS) dengan kualitas hidup pasien Benign Prostatic Hyperplasia (BPH) di Rumah Sakit Umum Daerah (RSUD) Arifin Achmad Provinsi Riau. Kata Kunci : Lower Urinary Tract Symptoms, Kualitas Hidup, Benigna Prostatic Hyperplasia